2011
DOI: 10.1089/brain.2011.0053
|View full text |Cite
|
Sign up to set email alerts
|

Structural Network Topology Revealed by White Matter Tractography in Cannabis Users: A Graph Theoretical Analysis

Abstract: Endocannabinoid receptors modulate synaptic plasticity in the brain and may therefore impact cortical connectivity not only during development but also in response to substance abuse in later life. Such alterations may not be evident in volumetric measures utilized in brain imaging, but could affect the local and global organization of brain networks. To test this hypothesis, we used a novel computational approach to estimate network measures of structural brain connectivity derived from diffusion tensor imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
6
24
1
Order By: Relevance
“…It is premature, although tempting, to speculate that mTBI poses no significant impact on the hubs regions based on the absence of differences in the distribution of hubs as seen in the present study. On the contrary, previous research has shown adverse effect of neurological disorders or disease in the absence of changes in the distribution of hubs [Kim et al, 2011; Liu et al, 2012]. Our analysis demonstrated evidence of abnormalities in nodal degree, nodal clustering coefficient, or nodal betweeness centrality in certain hubs including superior frontal gyrus, middle frontal gyrus, superior parietal gyrus, precuneus, supplementary motor area, and calcarine.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…It is premature, although tempting, to speculate that mTBI poses no significant impact on the hubs regions based on the absence of differences in the distribution of hubs as seen in the present study. On the contrary, previous research has shown adverse effect of neurological disorders or disease in the absence of changes in the distribution of hubs [Kim et al, 2011; Liu et al, 2012]. Our analysis demonstrated evidence of abnormalities in nodal degree, nodal clustering coefficient, or nodal betweeness centrality in certain hubs including superior frontal gyrus, middle frontal gyrus, superior parietal gyrus, precuneus, supplementary motor area, and calcarine.…”
Section: Discussioncontrasting
confidence: 75%
“…The concept of small-worldness originated in investigations of social network connectivity. When applied in neuroscience, the small-worldness and other measures based on graph theory analysis have shown to be sensitive to development [Bassett et al, 2011; Dennis et al, 2013; Hagmann et al 2010], cognitive ability [Ajilore et al, 2014; Reijmer et al, 2013; Vaessen et al, 2012; Vecchio et al, 2014] and impaired structural connectivity in various patient populations and conditions such as schizophrenia, Alzheimer’s disease, Parkinson’s disease, epilepsy, stroke, aging, and drug abuse [Bassett et al, 2008; Bernhardt et al, 2011; Daianu et al, 2013; Kim et al, 2011; Lo et al, 2010; Liu et al, 2008; Onoda and Yamaguchi, 2013; Shi et al, 2012; van Meer et al, 2012; Zalesky et al, 2011]. …”
Section: Introductionmentioning
confidence: 99%
“…68 All mathematical details can be found in previous studies. 65,69,70 As noted in van Wijk et al, 71 the proportion of the total connections can be varied to investigate the network properties by varying a threshold (ie, removing the weaker connections based on their weighting). In this study, we constructed networks over a range from 5% (sparse matrix including only strong connections) to 50% (dense matrix including weak connections) of connection density.…”
Section: Structural Connectivity and Network Analysismentioning
confidence: 99%
“…Marijuana users were also observed to have alteration in the PCC (Kim et al, 2011). Similarly, individuals with alcohol use disorder, (Chanraud, Pitel, Pfefferbaum, & Sullivan, 2011) reported desynchronized low frequency rs-fMRI signals from the PCC and cerebellum.…”
Section: Discussionmentioning
confidence: 87%
“…The PCC, a key region in the DMN is responsible for self‐consciousness and self‐referential mental thoughts (Andrews‐Hanna, Reidler, Sepulcre, Poulin, & Buckner, ; Andrews‐Hanna, Smallwood, & Spreng, ; Buckner & Carroll, ; Cavanna & Trimble, ; Fransson & Marrelec, ; Leech & Sharp, ; Raichle et al, ; Spreng, Mar, & Kim, ). Marijuana users were also observed to have alteration in the PCC (Kim et al, ). Similarly, individuals with alcohol use disorder, (Chanraud, Pitel, Pfefferbaum, & Sullivan, ) reported desynchronized low frequency rs‐fMRI signals from the PCC and cerebellum.…”
Section: Discussionmentioning
confidence: 99%